2001
DOI: 10.1176/appi.ps.52.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Related to Admission and Release Decisions in Psychiatric Emergency Services

Abstract: Guidelines addressing the variables that should be considered in making disposition decisions in psychiatric emergency services should be developed. The study found five variables that should be considered for inclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 25 publications
4
46
0
3
Order By: Relevance
“…While this study did not examine the factors that could mediate this relationship, past research has found an association between sleep problems and suicidal ideations and behaviors (13), which, in turn, are among the most common reasons for emergency department use and psychiatric hospitalization (14, 15). This and other potential mechanisms linking sleep problems with emergency service use and psychiatric hospitalization need to be assessed in future studies using a longitudinal design.…”
Section: Discussionmentioning
confidence: 94%
“…While this study did not examine the factors that could mediate this relationship, past research has found an association between sleep problems and suicidal ideations and behaviors (13), which, in turn, are among the most common reasons for emergency department use and psychiatric hospitalization (14, 15). This and other potential mechanisms linking sleep problems with emergency service use and psychiatric hospitalization need to be assessed in future studies using a longitudinal design.…”
Section: Discussionmentioning
confidence: 94%
“…A admissão em enfermaria psiquiátrica deverá ser considerada fortemente em casos de agitação psicomotora intensa, impulsividade irrefreável, risco de agressividade, risco ou tentativa de suicídio, diante da exposição a situações de risco, diante da falta de insight e/ou quando não houver continência/suporte familiar para a possibilidade de internação domiciliar e manejo extra-hospitalar. Esses fatores de risco compõem uma trama que deve servir como guia, uma vez que inexistem protocolos rígidos que possam defi nir a conduta de admissão (ou não) na emergên-cia psiquiátrica 44 . A prática clínica revela nuances que devem ser detalhados por uma equipe bem treinada e experiente.…”
Section: Fase De Recuperaçãounclassified
“…A number of studies examine clinical and non-psychiatric predictors of diagnostic and disposition decision-making for adult PES patients [13][14][15][16][17][18][19]. However, among studies on U.S. pediatric psychiatric emergency-type settings [20][21][22][23] even fewer have specifically examined the role of sociodemographic factors (e.g., race, ethnicity) in diagnostic and disposition decision-making.…”
Section: Introductionmentioning
confidence: 99%